Ethical rehabilitation after the Holocaust - Wilson, Paul E. (Palgrave Macmillan, 2024)
Zusammenfassung: Genocide murders innocents in a society, and it leaves behind moral corruption and societal twistedness. A genocide like the Holocaust can happen only if the normative ethical commitments to honor the fundamental right to life are compromised or abandoned. When a society lives through a genocide, the moral imagination of peoples and collectives, their ethical behaviors, and even the underlying social contract become twisted and broken. Societies and individuals caught within a genocide need an ethical rehabilitation to move a post-genocidal society out of its ethical degradation. This book discusses the steps of transitional justice as ethical ways to move individuals and societies away from lingering injustices and toward an equilibrium of justice. Paul E. Wilson is a faculty member and Program Coordinator for Shaw University, where he has taught religion and philosophy classes for the past thirty-two years. His monograph, The Degradation of Ethics Through the Holocaust, was published by Palgrave in 2023
Keywords: Ethics.; World War, 1939-1945.; Political science.; Peace.; Rehabilitation; Judenvernichtung; Transitional Justice; Ethik; Moral Philosophy and Applied Ethics.; History of World War II and the Holocaust.; Political Theory.; Peace and Conflict Studies.